Pemanfaatan Tepung Bekatul Sebagai Substitusi Bahan Pembuatan Stik Bawang - Rahmawati, Fajar Tri; Putri, Meddiati Fajri (Food Science and Culinary Education Journal, 2023)
Stick is one of cake’s type that flat, long, like a cane, has a savory taste, has a crispy texture and the final process is through frying (Fransiska 2019). The aims of this study was to the determine the level of community interested for the experimental and brand stick on the stick product, make certain about the total food fiber content in the experimental stick, and calculate the selling price in the experimental sticks. The research method used is a descriptive analysis of the percentage using microsoft excel aplications, laboratory tests to determine the total nutritional content of food fiber using AOAC gravimetry, and calculating the selling price using the Break Event Point (BEP) analysis. The results showed that the most preferred brand was brand B. Laboratory test results of the average total food fiber content in sticks sequentially showed that bran flour substitution was 0% (9,66%), 6% (9,94%), 8% (16,07%) and 10% (17,87%). The results of the calculation of Break Event Point (BEP) on the stick with a 10% substitution of bran flour with sales of Rp.70.794.800 and can be reached in 191 days.